Integrated circuit and system design power and timing modeling, optimization, and simulation, 21st International Workshop, PATMOS 2011, Madrid, Spain, September 26-29, 2011, proceedings - Ayala, Jose L.; García-Camara, Braulio; Prieto, Manuel; Ruggiero, Martino; Sicard, Gilles (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 21st International Conference on Integrated Circuit and System Design, PATMOS 2011, held in Madrid, Spain, in September 2011. The 34 revised full papers presented were carefully reviewed and selected from numerous submissions. The paper feature emerging challenges in methodologies and tools for the design of upcoming generations of integrated circuits and systems and focus especially on timing, performance and power consumption as well as architectural aspects with particular emphasis on modeling, design, characterization, analysis and optimization.